PELAYANAN PENGADAAN AIR BERSIH OLEH UNIT PELAKSANA TEKNIS (UPT) AIR MINUM KOTA DUMAI TAHUN 2011-2012 - Elfany Nasti; M.Y. Tiyas Tinov (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
Clean water is a very important requirement for human survival. However, the availability of clean water, especially in urban areas nowadays is hard thing to come by. The existence of water in urban areas is very important considering the activity of urban life are very dynamic. To meet the need for clean water, resident of urban areas can not rely on water from direct rainfall and surface water such as water sources has largely been contaminated either directly or indirectly from human activity itself.Given the scale of the role and function of clean water as well as to anticipate the high demand for water, especially clean water in urban areas, to meet the water needs of the built urban water management managed by the State-Owned Enterprises (SOE) is the Regional Water Company.The agency responsible for services and levy issues of clean water, but at this time the performance of certain services and levy water in urban areas is still lacking. The agency is also responsible for preparing and providing clean water and distribute it to the public (costumers) as a consumer.The study was conducted using a quality approach. Techniques used in collecting data on the qualitative research are interviews and documentation. The data has been collected and processed qualitatively.Beside on this study, it can be concluded that provision of water services in the Dumai city not run optimally because there are some constraints inters of both the proposition and infrastructure.Through this paper the author will describe the constraints that exist in the provision of water services by the Technical Implementation Unit of Dumai City.KeyWords: services, local government, the Technical Implementation Unit of Dumai City, public, the consumer.